ANALISIS KESALAHAN MAHASISWA DALAM MENYELESAIKAN SOAL INDUKSI MATEMATIKA - Mardiyah, Ainil (JURNAL LEMMA, 2024)
This research aims to describe the types of student errors and the causes of errors made by students in solving mathematical induction problems. This type of research is descriptive research with a qualitative approach. The subjects in this research were mathematics education study program students taking number theory courses for the 2020/2021 academic year. The data collection techniques used were tests and interviews, while the instruments used were mathematical induction test questions. Data analysis techniques are carried out by reducing data, presenting data and drawing conclusions. Based on data analysis, the results of this research show that factual errors were 4%, conceptual errors were 42%, principle errors were 45%, which was the most common error, and operational errors were 37%.  The cause of students making mistakes is students' lack of understanding of the concept of proof using mathematical induction and lack of accuracy in answering questions and using arithmetic operations.